Enhancing oral health outcomes through public health policy reform - Chukwuemeka L. Anyikwa; Chukwuebuka E. Ogwo (Frontiers in Oral Health)
This article explores the transformative potential of public health policies to improve oral health outcomes through the integrated application of three fundamental pillars: sustainability, equity in healthcare access, and the reduction of oral health disease burden. By examining the interplay of these pillars, the discussion proposes strategies that not only enhance preventive measures and accessibility to dental care but also foster long-term, sustainable improvements in population oral health. The framework presented herein is intended to guide policymakers in creating evidence-based interventions that address disparities and mitigate the growing burden of oral diseases globally.